Fechamento de mina e a reabilitação do espaço urbano afetado - Gabriela Salazar Silva Pinto (2017)
The existence of mining activities within urban areas or urban expansion areas is part of the Brazilian reality (from the north to the south of the country). Even though the mining operations can be characterized as long-term activities, the decommission of the activities and the mining closure are inevitable phases of these enterprises due to the future depletion of the mineral reserves.Therefore, the reabilitation of the urban areas affected by the mining activities and the future usage of the mined area represent the main concerns of the community that surrounds the mining enterprise. This research is aimed at analysing the normative and theoretical possibilities for the determination of obligations and benefits to the entrepreneur in charge of the mine closure within urban areas or urban expansion areas in order to execute the reabilitation of the urban environment and future usage of the urban area in favor of the community affected by the enterprise. The methodological path followed under the scope of this research comprises the analysis of practical cases, doctrine, legislation and judicial decisions applicable to the subject. Lastly, there will be presented some proposals in order to enable that the mine closure within urban areas results in opportunities for the surrouding community.